2018
DOI: 10.26434/chemrxiv.7043927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of Phosphonic Acid Ligands for Nanocrystal Surface Functionalization and Solution Processed Memristors

Abstract: <p>Here we synthesize 2-ethylhexyl, 2-hexyldecyl, 2-[2-(2-methoxyethoxy)ethoxy]ethyl, oleyl and <i>n</i>-octadecyl phosphonic acid and use them to functionalize CdSe and HfO<sub>2</sub> nanocrystals. In contrast to branched carboxylic acids, post-synthetic surface functionalization of CdSe and HfO<sub>2</sub> nanocrystals is readily achieved with branched phosphonic acids. A simple flow coating process is used to deposit ribbons of individual phosphonic acid capped HfO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…To exchange the oleates for 1, we only added a slight excess of 1 because phosphonates have a stronger binding affinity to the NC surface. 67,[69][70] Figure 4C). This is also reflected in the single exponential fit of the DOSY decay curve for the region from 1.7 to 1.2 ppm ( Figure 4D).…”
Section: Main Textmentioning
confidence: 98%
See 1 more Smart Citation
“…To exchange the oleates for 1, we only added a slight excess of 1 because phosphonates have a stronger binding affinity to the NC surface. 67,[69][70] Figure 4C). This is also reflected in the single exponential fit of the DOSY decay curve for the region from 1.7 to 1.2 ppm ( Figure 4D).…”
Section: Main Textmentioning
confidence: 98%
“…Ligands with multiple ethylene glycol moieties are highly versatile since they provide colloidal stability in a variety of solvents with different polarity, excluding hexanes. 17,[66][67][68] Since poly(ODE) is highly soluble in hexanes, this provides a pathway to separate poly(ODE) from the NCs.…”
Section: Main Textmentioning
confidence: 99%
“…A similar result in terms of shape control was achieved in a more recent work, 45 in which custom-synthesized oleylphosphonic acid was used. 46 The main advantage of using oleylphosphonic acid in lieu of alkyl phosphonic acids is that the former are much more soluble in the nonpolar or moderately polar solvents used to prepare colloidally stable suspensions of nanocrystals, and this has remarkable consequences over the stability of nanocrystals under air: when colloidal suspensions of nanocrystals prepared using alkyl phosphonic acids are exposed to air, the protonation of the hydrogen phosphonates due to moisture should transform them into charge-neutral phosphonic acids, which get detached from the surface of the nanocrystals and, being insoluble, precipitate. This process slowly destabilizes the nanocrystals, which aggregate over time.…”
Section: Changing Color By Shapementioning
confidence: 99%
“… 12 This is due, most likely, to the fact that OLPA molecules are characterized by the presence of a double bond, so that intermolecular London forces are weaker and their melting points are lower than in the case of phosphonic acids with linear and saturated alkyl chains. 22 , 23 Three NC samples were prepared by performing the synthesis at 100 °C and varying the reaction time from 45 to 600 s (see the experimental section for details). The XRD analysis confirmed that all the NC products have the expected orthorhombic CsPbBr 3 perovskite structure (ICSD number 98751) with no presence of impurities ( Figure 1 d).…”
mentioning
confidence: 99%
“…Both 1 H and 31 P NMR spectra of quantum confined LHP NCs evidenced the presence of P-based molecules bound to the surface of the NCs: both alkenyl protons (9,10) at 5.3 ppm ( Figure 2 a) and phosphorus signals peaks in the range 10–40 ppm ( Figure 2 b) were broadened with respect to those of free OLPA ligands ( Figure S3 and S10 ), an indication that these P-based molecules have a longer correlation time (τ c ) as a consequence of their binding to NCs’ surface. 23 Also, the presence of multiple 31 P signals was a mark of a complex ligand–surface interaction, with surface molecules adopting different binding motifs with Pb 2+ cations.…”
mentioning
confidence: 99%